Občestvena duhovnost svetih bratov Cirila in Metoda - Platovnjak, Ivan (Edinost in dialog, 2013)
At the beginning of the third millennium, the contemporary Pope at the time, John Paul II, encouraged the entire Catholic Church to make communal spirituality one of its main tasks. He considered this the only way the Catholic Church could become a home and school of a community and thus fulfill its fundamental mission in the given time and space. In his discussion, the author argues that the core elements of this spirituality may already be observed in the lives, teachings, and work of saintly brothers Cyril and Methodius and that it was the choice of this spiritual journey that enabled them to perform their mission among the Slavs successfully. The author briefly discusses the core elements of their spiritual journey, which confirm the hypothesis suggested. These elements are the following: love to the Holy Trinity and the preference of the communal following of Christ rather than a solitary one; the awareness of fundamental equality and the brotherhood of all in Christ; the conviction about the need for sharing goods; respectful dialog with every person, even with an opponent; the conviction that we can only grow on the journey to sanctlity with our brothers and sisters. Therefore, the saintly brothers may be considered a role model for the entire Church and provide it with spiritual support in fulfilling its mission.
Keywords: Cyrillus, svetnik, 826-869; Methodius, svetnik, 815-885; krščanska duhovnost; občestvo; svetniki